2003
DOI: 10.1128/jb.185.5.1642-1649.2003
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnogalacturonate Lyase RhiE Is Secreted by the Out System in Erwinia chrysanthemi

Abstract: Supernatants of rhamnose-induced Erwinia chrysanthemi strain 3937 cultures contain a principal secreted protein named RhiE. A rhiE mutant has been found among a set of rhamnose-induced MudI1681 lacZ fusions. RhiE is a 62-kDa protein that has rhamnogalacturonate lyase activity on rhamnogalacturonan I (RG-I). It does not require a divalent cation for its activity and has an optimal pH of 6.0. rhiE expression is strongly induced in the presence of rhamnose but is also regulated by PecT and Crp, two regulators of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 35 publications
0
33
0
2
Order By: Relevance
“…In their active form, pectate lyases contain at least one bound calcium ion, which plays an integral part in substrate binding and activation [33]. Though present evidence suggests that calcium ions are not strictly required for the catalytic activity of polysaccharide lyase family 4 [34,35], the calcium ion may have a unique structural role explaining its positive effects on catalysis.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In their active form, pectate lyases contain at least one bound calcium ion, which plays an integral part in substrate binding and activation [33]. Though present evidence suggests that calcium ions are not strictly required for the catalytic activity of polysaccharide lyase family 4 [34,35], the calcium ion may have a unique structural role explaining its positive effects on catalysis.…”
Section: Discussionmentioning
confidence: 70%
“…Low domain I homology (4-9% identity) between fungal and plant sequences may indicate an evolutionary divergent sub-family in which the catalytic machinery has been maintained, while the substrate recognition has undergone major modifications. RhiE, a bacterial RG-lyase from Erwinia chrysanthemi, is more related (18-22% identity) to the A. thaliana MYST sequences than to A. aculeatus RG-lyase (7% identity) and has been shown to cleave to RG-I backbone by a b-elimination mechanism [35]. Such sequence diversity in polysaccharide lyase family 4 may reflect variation in the pattern of arabinose and galactose branching side chains of RG-I from different species.…”
Section: Conserved Residues In Polysaccharide Lyase Familymentioning
confidence: 99%
See 1 more Smart Citation
“…This phase of colonization is followed by the symptomatic phase of the disease only when environmental conditions are favorable for massive bacterial multiplication and production of plant cell wall-degrading enzymes (41). E. chrysanthemi produces different types of pectinases: pectin methyl esterases, pectin acetyl esterases, exo-and endopectate lyases, exopolygalacturonases, and a rhamnogalacturonate lyase (25,51). All of these enzymes have the potential to degrade different parts of pectin, including the linear and branched regions, but are not equally involved in symptom initiation and spreading (3,5,27).…”
mentioning
confidence: 99%
“…Previous studies showed that E. chrysanthemi is able to degrade and catabolize a range of plant structural polysaccharides, including linear regions of pectin and the backbone of the ramified regions RGI (19,21,28). Galactans are constituents of the side chains attached to RGI.…”
Section: Discussionmentioning
confidence: 99%